Effects of green synthesised silver nanoparticles (ST06-AgNPs) using curcumin derivative (ST06) on human cervical cancer cells (HeLa) in vitro and EAC tumor bearing mice models [Corrigendum] - Murugesan K (Dove Medical Press, 2019)
Murugesan K, Koroth J, Srinivasan PP, et al. Int J Nanomedicine. 2019;14:5257–5270.Following a review of our post-publication, we found the presentation of affiliations 2 and 4 are incorrect. They are currently listed as: 2Department of Pharmaceutical Chemistry, Manipal Academy of Higher Education, Manipal 576104, Karnataka, India; 4KLE Academy of Higher Education & Research, KLE College of Pharmacy, Bangalore, KN, India. The correct presentation is: 2Manipal Academy of Higher Education, Manipal 576104, Karnataka, India; 4Department of Pharmaceutical Chemistry, KLE Academy of Higher Education & Research, KLE College of Pharmacy, Bangalore, KN, India. The authors apologize for this error.Read the original article